Polyphenols in Food: Cancer Prevention and Apoptosis Induction - Sharma, Ashita; Kaur, Mandeep; Katnoria, Jatinder K.; Nagpal, Avinash Kaur (Current Medicinal Chemistry, 2018)
Polyphenols are a group of water-soluble organic compounds, mainly of natural origin. The compounds having about 5-7 aromatic rings and more than 12 phenolic hydroxyl groups are classified as polyphenols. These are the antioxidants which protect the body from oxidative damage. In plants, they are the secondary metabolites produced as a defense mechanism against stress factors. Antioxidant property of polyphenols is suggested to provide protection against many diseases associated with reactive oxygen species (ROS), including cancer. Various studies carried out across the world have suggested that polyphenols can inhibit the tumor generation, induce apoptosis in cancer cells and interfere in progression of tumors. This group of wonder compounds is present in surplus in natural plants and food products. Intake of polyphenols through diet can scavenge ROS and thus can help in cancer prevention. The plant derived products can also be used along with conventional chemotherapy to enhance the chemopreventive effects. The present review focuses on various in vitro and in vivo studies carried out to assess the anti-carcinogenic potential of polyphenols present in our food. Also, the pathways involved in cancer chemopreventive effects of various subclasses (flavonoids, lignans, stilbenes and phenolic acids) of polyphenols are discussed.
Keywords: lignans